Strategic Priorities for the Indian Telecom Industry in the Next Decade - Sarda, Anupam; Arun Kumar, V.; Chetia, Bikram; Gangapuram, Rohini; Taneja, Sippy; Jayaraman, R. (Prabandhan: Indian Journal of Management, 2013)
The Indian Telecom Success Story in India is a feather in the caps of several stakeholders, principally the government, followed by the private sector players who have invested over 200 K crores to take advantage of the policy environment created by the government to set up large telecom networks in the country, and provide one of the best telecom services comparable to the best in the world. The mushrooming of services, devices, telecom towers, use of diesel have all brought in their wake, some issues as well, although the low cost of the voice services - said to be the lowest in the world - has washed away much of the criticism. In this paper, the authors trace the development of the Indian telecom industry. They developed a PESTEL framework, a Porter's Five Forces Field analysis framework, did a SWOT analysis, used the BCG Matrix - all to analyze and highlight the many aspects of this growing industry. These analyses provide some insights into the workings of the industry. The authors concluded that the way forward will include more attention to VAS products, more of 3G and 4G applications development, more newproduct development suitable for the B to C, and in the inter-industry domains where B to B applications will have to propel growth in a world with increasing automation and mobile phone usage in day to day life activities.